Efficiency evaluation of leaded glasses and visors for eye lens dose reduction during fluoroscopy guided interventional procedures. (August 2022) - Samara, Eleni Theano; Cester, Davide; Furlan, Miha; Pfammatter, Thomas; Frauenfelder, Thomas; Stüssi, Anja
Highlights: Eye protective equipment is essential for fluoroscopy guided interventional procedures. Full visors may be more effective than lead glasses as their large coverage area absorbs more scattered irradiation. Spatial dose distribution over the visor is provided. Abstract: Purpose: Fluoroscopy guided interventional procedures guarantee high benefits for patients, but are associated with high levels of radiation exposure for the medical staff. Their increasing use and complexity results in even higher radiation exposures, with a risk to exceed the annual dose limit of 20 mSv for the eye lens. The aim of the study was to evaluate the potential dose reduction of eye lens exposure for lead glasses and for two types of visors (half and full), used by physicians performing interventional procedures. Methods: Eye lens dose measurements were carried out on an anthropomorphic phantom simulating a physician performing a fluoroscopy guided interventional procedure. Dose reduction factors were calculated using high sensitivity thermoluminescent dosimeters. Moreover, a spatial dose distribution was generated for the two visors. Results: The dose reduction coefficient was found to be 1.6 for the glasses, 1.2 for the half visor and 4.5 for the full visor. Conclusions: Optimal radiation protection requires a combination of different radiation protection equipment. Full visors that cover all the face of the operator are recommended, as they absorb scattered radiation reaching the eyes from all directions. Full visors should be prioritized over radiation protection glasses for cases where other protective equipment such as ceiling shielding cannot be used.